Decoupling of Au and As during rapid pyrite crystallization - Wu, Y.; Evans, Katy; Hu, S.; Fougerouse, Denis; Zhou, M.; Fisher, L.A.; Guagliardo, P.; Li, J. (GEOLOGICAL SOC AMER, INC, 2021)
Gold (Au) is largely hosted by pyrite in a variety of hydrothermal systems, but the incorporation of Au into pyrite under disequilibrium conditions remains poorly understood. We integrate synchrotron X-ray fluorescence microscopy, electron backscatter diffraction, nanoscale secondary ion mass spectrometry, and laser ablation–multicollector–inductively coupled plasma–mass spectrometry to constrain the processes that sequester Au into zoned pyrite in the hydrothermal cement of breccia ores from the world-class Daqiao orogenic Au deposit, central China. Euhedral pyrite cores with oscillatory and sector zoning, variable δ34S values, and lower Au-As contents than the mantles are attributed to crystallization during oxidation of metal-depleted ore fluids with local variation in fluid conditions. The isotopically uniform colloform mantles are formed by pyrite crystallites separated by low-angle boundaries and are characterized by unusual decoupling of Au and As. Mantle formation is attributed to rapid disequilibrium precipitation from a metal-rich FeS2-supersaturated fluid. Incorporation of Au into the pyrite mantles was facilitated by abundant lattice defects produced by rapid nucleation. Gold-As–poor pyrite rims were deposited from an evolved ore fluid or other metal-depleted fluids. These results show that chemical variations recorded by fine layering within minerals can provide valuable insights into disequilibrium mass transfer and ore formation. The decoupling between Au and As in pyrite mantles indicates that As is not always a reliable proxy for Au enrichment in rapidly crystallized porous pyrite.